2020
DOI: 10.1096/fj.201902478r
|View full text |Cite
|
Sign up to set email alerts
|

Immune changes in peripheral blood and hematoma of patients with intracerebral hemorrhage

Abstract: Immunologic changes in the hematoma of patients with intracerebral hemorrhage (ICH) and the contribution of these changes to prognosis are unknown. We collected the blood samples and hematoma fluid from 35 patients with acute ICH (<30 hours from symptom onset) and 55 age-matched healthy controls. Using flow cytometry and ELISA, we found that the percentages of granulocytes, regulatory T cells, helper T (Th) 17 cells, and dendritic cells were higher in the peripheral blood of patients with ICH than in healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 94 publications
(303 reference statements)
2
45
0
Order By: Relevance
“…Relevant evidence indicated that the peripheral cellular immune system changed dramatically in the immediate aftermath of ICH (23). Therefore, changes in specific inflammatory markers in the peripheral blood are an indicator of the severity of the primary injury, theoretically.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant evidence indicated that the peripheral cellular immune system changed dramatically in the immediate aftermath of ICH (23). Therefore, changes in specific inflammatory markers in the peripheral blood are an indicator of the severity of the primary injury, theoretically.…”
Section: Discussionmentioning
confidence: 99%
“…In brain parenchyma, M1 microglia are the major source of inflammatory mediators, such as IL-1β, IL-6, IL-12, IL-23, and TNF-α (Jiang et al, 2020 ). Although inflammation is essential for innate immunity, it is the chief culprit to the sustained neurological deterioration in a sterile environment (Zhu et al, 2019 ).…”
Section: Functions Of Activated Microglia After Ichmentioning
confidence: 99%
“…Both preclinical and clinical studies suggest that microglia/macrophage-mediated inflammatory response plays an important role in hemorrhage-induced brain damage [ 64 , 65 ]. ICH results in very profound activation of microglia/macrophages, highly plastic cells, which display diverse phenotypes [ 66 ].…”
Section: Microrna and Ich-induced Neuroinflammationmentioning
confidence: 99%